ZARZĄD WSPÓLNOTĄ GRUNTOWĄ - Jędrejek, Grzegorz (Zeszyty Prawnicze, 2017)
The Management of a Joint Land Property Summary The article is devoted to the concept of a joint land property, the origins of which go back to the enfranchisement performed on the Polish territory in the XIXth century, which consisted in granting the property right to the hitherto users. The problem of pieces of land which were used commonly by the village’s inhabitants was solved in this manner that some parts of it were the subject of a real easement and other parts were left in the inhabitants’ hands establishing so called a joint land property. The article presents the problems connected with the management of the joint land property. The postulates de lege ferenda have been also formulated. The author suggests the elimination of the partnerships, the establishment of which is obligatory, aimed at managing the joint land properties. In his opinion respective provisions of the Civil Code related to co-ownership should apply thereto.